Respuesta :

Answer:

[tex]a = p*q\\b = (p*s)+(q*r)\\c = r*s[/tex]

Step-by-step explanation:

The standard form of trinomial is given as:

[tex]ax^2+bx+c[/tex]

And the factored form is:

[tex](px+r)(qx+s)[/tex]

In order to find the values of a,b and c in terms of p,q,r and s we will take the factored form, multiply it and then compare it with the standard form.

So,

[tex](px+r)(qx+s)\\=px(qx+s)+r(qx+s)\\= pqx^2+psx+qrx+rs\\= pqx^2+(ps+qr)x+rs[/tex]

Now comparing it with the standard form of trinomial

We will compare the co-efficients of x^2, x and the constant

By comparing, we get

[tex]a = pq = p*q\\b = ps+qr = (p*s)+(q*r)\\c = rs = r*s[/tex]

Hence,

[tex]a = p*q\\b = (p*s)+(q*r)\\c = r*s[/tex]